(3GdELGHGJ GdfehPLjI ddfLGM aj GdebGHdGJ GdTNUjI (B/s - (3aQGj, Qhfs ((3GdbGgQI(B: s (3OGQ GdaGQhb ddfTQ hGdJhRjY(B, s, 2006)
(3jVe eYQaI GdPGJ, GJNGP NWhGJ LOjI, GdJYQa Ydi GdBNQ, GdJYGed eY eTcdI fbU GdNHQI, NHQGJ GdYed, GdJQcjR Ydi CehQ eMOOI, eYdheGJ Yf GdhXjaI GdSGHbI, CSHGH GNJjGQ GdTQcI, GdCSFdI GdeMXhQI aj GdebGHdGJ GdTNUjI, GdCSFdI GdNJGejI(B.s
Keywords: (3GdJhXjas; (3JhXja(B- (3ebGHdGJs